Beneficial Effects of a Dietary Weight Loss Intervention on Human Gut Microbiome Diversity and Metabolism Are Not Sustained during Weight Maintenance - Heinsen, Femke-Anouska; Fangmann, Daniela; Müller, Nike; Schulte, Dominik M.; Rühlemann, Malte C.; Türk, Kathrin; Settgast, Ute; Lieb, Wolfgang; Baines, John F.; Schreiber, Stefan; Franke, Andre; Laudes, Matthias (Obesity facts, 2016)
Objective: In the present study, we examined the effect of a very low-calorie diet(VLCD)-based obesity program on human gut microbiome diversity and metabolism during weight loss and weight maintenance. Methods: Obese subjects underwent 3 months of VLCD followed by 3 months of weight maintenance. A lean and an obese control group were included. The microbiome was characterized by performing high-throughput dual-indexed 16S rDNA amplicon sequencing. Results: At baseline, a significant difference in the Firmicutes/Bacteroidetes ratio between the lean and obese individuals was observed (p = 0.047). The VLCD resulted in significant alterations in gut microbiome diversity from baseline to 3 months (p = 0.0053). Acinetobacter represented an indicator species for the observed effect (indicator value = 0.998, p = 0.006). Metabolic analyses revealed alterations of the bacterial riboflavin pathway from baseline to 3 months (p nom = 0.0078). These changes in diversity and bacterial metabolism induced by VLCD diminished during the weight maintenance phase, despite sustained reductions in body weight and sustained improvements of insulin sensitivity. Conclusion: The present data show that a VLCD is able to beneficially alter both gut microbiome diversity and metabolism in obese humans, but that these changes are not sustained during weight maintenance. This finding might suggest that the microbiome should be targeted during obesity programs.